S55 Ward-based high flow nasal cannula oxygen – the south west experience. (12th November 2019) - Jones, RC; Dipper, A; Morrison, H
Abstract : High flow nasal cannula (HFNC) oxygen is increasingly used to deliver higher concentrations of humidified oxygen to patients than conventional oxygen therapy. Data on indications and outcomes is limited. Existing studies observe heterogenous populations, including post-operative and critical care patients. We sought to evaluate outcomes for adult medical inpatients commenced on HFNC across the South West region. Methods: Data was collected prospectively on all medical inpatients >18 years old commenced on HFNC from 9 centres across the South West. The first data collection period ran for 14 days in November 2018 and a second period of 28 days ran during February/March 2019. We looked at indications, treatment escalation trends and mortality. Results: 43 patients were started on HFNC. Age range was 29–91 (mean 64 years). The indication was acute type 1 respiratory failure in 40/43 cases, with hypercapnic respiratory failure in patients. Table 1 outlines the primary diagnosis. 86% of patients had an escalation status recorded prior to commencing HFNC. The overall in-hospital mortality rate was 30% and the 30-day mortality was 37%. For patients who were not suitable for full escalation of care, mortality was 50%. In total, 8 patients (19%) were referred to palliative care. There was no difference in mortality based on primary diagnosis, number/type of co-morbidities or oxygen level on pre-HFNC blood gas. Conclusions: This was a prospective, multicentre review of HFNC in a ward setting. Overall mortality rates for patients requiring HFNC in our population are similar to those reported for patients requiring acute non-invasive ventilation (NIV). 1 Mortality rates are higher in those patients who are not suitable for full escalation of treatment. This may guide clinical decision making and inform discussions in patients with limited escalation options. Given the significant mortality, it is important that HFNC is subject to the same audit and quality procedure as NIV. On Behalf of PRISM, Trainee Research Network, South West. Reference: Juniper, et al . Inspiring change: a review of the quality of care provided to patients receiving non-invasive ventilation. London. NCEPOD. 2017.